Global boron cycle in the Anthropocene. Issue 2 (19th February 2016) - Schlesinger, William H.; Vengosh, Avner
Abstract: This paper presents a revised and updated synthesis of the biogeochemical cycle of boron at the Earth's surface, where the largest fluxes are associated with the injection of sea‐salt aerosols to the atmosphere (1.44 Tg B/yr), production and combustion of fossil fuels (1.2 Tg B/yr), atmospheric deposition (3.48 Tg B/yr), the mining of B ores (1.1 Tg B/yr), and the transport of dissolved and suspended matter in rivers (0.80 Tg B/yr). The new estimates show that anthropogenic mobilization of B from the continental crust exceeds the naturally occurring processes, resulting in substantial fluxes to the ocean and the hydrosphere. The anthropogenic component contributes 81% of the flux in rivers. The mean residence time for B in seawater supports the use of δ 11 B in marine carbonates as an index of changes in the pH of seawater over time periods of > 1 Ma. Key Points: Major human impacts on the annual global flux of boron Atmospheric budget for boron is unbalanced Boron isotopes useful for paleoreconstructions at >1 Ma timescales